Islamic Ethical Values in Islamic Bank Management: A Literature Analysis of the Concepts of Trust and Justice - St. Wijdanah Ram; Jenuri, Jenuri; Muh. Irwin (CV. ULIL ALBAB CORP, 2025)
This study examines the ethical foundations of Islamic banking management through the integration of the values ​​of amanah (trust) and 'adl (justice), the main moral pillars of Islam. Despite the rapid growth of the Islamic banking industry, a gap remains between the ideals of Islamic principles and the reality of managerial implementation, where profit-oriented practices often override ethical considerations. Using a qualitative literature research approach, this study systematically reviews the academic literature to explore how the values ​​of amanah (trust) and justice are operationalized within the strategic and managerial frameworks of Islamic banks. The analysis reveals that previous studies tend to discuss these two values ​​separately without highlighting their synergy and interdependence in forming an integrative ethical governance model. Amanah (trust) is embodied in transparency, accountability, and fiduciary responsibility, while justice is reflected in proportional profit sharing, equal treatment, and fair financial inclusion. The integration of these two values ​​within the framework of Sharia governance and stakeholder theory forms a distinctive managerial ethic that distinguishes Islamic banks from conventional systems. This conceptual synthesis provides theoretical contributions to the study of Islamic management as well as practical recommendations for strengthening ethical sustainability in Islamic financial institutions.